HIV viral load monitoring during monkeypox virus infection among people with HIV - Raccagni, Angelo Roberto; Mileto, Davide; Galli, Laura; Bruzzesi, Elena; Canetti, Diana; Rizzo, Alberto; Bertoni, Costanza; Clemente, Tommaso; Alberton, Francesca; Castagna, Antonella; Nozza, Silvia (AIDS (London), 2023)
Aims of this study were to assess the characteristics of Mpox among people with HIV (PWH) and describe the change of some immune-virological parameters during Mpox virus infection. Case series of PWH diagnosed with Mpox between May and July 2022 at the Infectious Diseases Unit of San Raffaele Scientific Institute, Milan, Italy. Real-time PCR was used to detect Mpox virus on oropharyngeal, cutaneous, genital and rectal swabs, plasma, seminal fluids, and urines. The values of the CD4 + lymphocytes and HIV-RNA were assessed both at Mpox diagnosis and after Mpox virological clearance and were compared to those prior to Mpox. The relationship between the symptoms clinical duration of Mpox and the CD4 + cell count at diagnosis was assessed with Spearman's correlation coefficient. Overall, 28 PWH on antiretroviral therapy with Mpox were evaluated. HIV-RNA did not substantially change at Mpox infection with respect to previous virological profile ( P  = 0.721). However, at time of Mpox diagnosis, we observed a detectable HIV-RNA (196 copies/ml) in one individual previously undetectable (HIV-RNA < 20 copies/ml) and an increase to 1.220 copies/ml in a previously viremic subject (HIV-RNA = 263 copies/ml). No significant differences in CD4 + cell count were found before and at time of Mpox diagnosis ( P  = 0.151) and a higher CD4 + cell count at Mpox diagnosis was marginally related to a lower duration of Mpox symptoms ( r  = -0.341, P  = 0.068). Among PWH, we advise monitoring HIV viral load at Mpox diagnosis and during follow-up, as well as providing counseling on the results, due to the important individual and community implications.